Filogenia molecular e revisão taxonômica de hemiancistrus bleeker, 1862 (Siluriformes : loricariidae) - Meza-Vargas, Sonia Vanessa (2020)
Hemiancistrus has a complex history, both taxonomic and phylogenetically. Since the description of Hemiancistrus in the XIX Century, the lack of precision in the diagnostic traits of the genus contributed to the confusion with other genera until today. Currently, Hemiancistrus has 12 valid species widely distributed in South America. Although the last study of the genus represents a considerable advance, there is still difficulties to identify them correctly. Aiming at having a better understanding of Hemiancistrus and related taxa, a molecular-based phylogenetic and a taxonomic revision are presented. The phylogeny is based on seven molecular markers, four mitochondrial (16S, coI, cytb e nd2) and three nuclear (rag1, rag2 e myh6), and the data matrix is composed by 107 terminals. The ingroup contains several genera of Hypostominae, including all species of Hemiancistrus, and the outgroup contains representatives of other subfamilies in Loricariidae. Bayesian Inference and Maximum Likelihood analyses were conducted using a concatenated data matrix of 5,467 characters. Both analyses were highly congruent and recovered Hemiancistrus polyphyletic. The results served as a basis to support propositions of new genera. The Hemiancistrus Clade includes Baryancistrus, `Baryancistrus` demantoides (Orinoco), Hemiancistrus, Panaque, Parancistrus, and Spectracanthicus. In this clade, Hemiancistrus is monotypic, only including the type species, and the `B.` demantoides species group represents a new genus composed of four species. Also, `H.` landoni and `H.` furtivus (Pacific), belonging to the Peckoltia Clade, are described as another new genus. The tribe Hypostomini is composed by `Hemiancistrus` cerrado (Tocantins), the clade `Hemiancistrus` chlorostictus (South), with six nominal species, Hypostomus, `Hypostomus` annectens, and Pterygoplichthys. Both clades H.` chlorostictus (South) and `H.` cerrado (Tocantins) are also described as new genera. Descriptions of all new genera are provided based on external morphological characters, as well as redescriptions and taxonomic comments of all of their species. Geographic distribution maps and identification keys are given for the `B.` demantoides and H.` chlorostictus species groups. Finally, members of the Hypostomini and valid species for Baryancistrus are discussed.